Susceptibility of lesser mealworm, Alphitobius diaperinus Panzer (Coleoptera: Tenebrionidae) to entomopathogenic fungi isolated from poultry houses litter and nearby soil - Popowska-Nowak, Elżbieta; Tumialis, Dorota; Pezowicz, Elżbieta (Studia Ecologiae et Bioethicae, 2017)
The lesser mealworm Alphitobius diaperinus is present in great numbers in poultry houses. These insects are especially dangerous as potential carriers of pathogens such as bacteria, viruses and parasites. We explored the possibility of using local strains of entomopathogenic fungi isolated from litter and from soil to control lesser mealworm populations. Isolated fungi showed low pathogenicity to lesser mealworm beetles. Infection with a suspension at a concentration of 1 × 108 spores/ml resulted in only 4 Metarhizium anisopliae sensu lato isolates showing the highest insect mortality in the range of 30–36%. Still lower pathogenicity was found in isolates of Beauveria bassiana, with only 4 isolates of B. bassiana causing a mortality of 17–26%. Isolates of Isaria fumosorosea and I. farinosa did not cause mortality in beetles that differed significantly from that in the control variant. The larvae were more susceptible to infection. Except for I. fumosorosea, all species caused 100% mortality in larvae. For further studies, the B. bassiana 3K isolate (from the litter) could be selected because of its high mortality (100%) and high larval infectivity (50% overgrown with mycelium).